2022
DOI: 10.1002/hsr2.502
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vaginal washing before Misoprostol insertion on cervical ripening before induction of labor: A randomized single‐blind clinical trial

Abstract: Background Vaginal pH is acidic in pregnancy, but there is no information about pH changes in pregnancy, and contradictory results have been reported from the effectiveness of Misoprostol at different vaginal pH. This study aimed to evaluate the effect of vaginal washing before Misoprostol insertion on cervical ripening before induction of labor in comparison with the control group. Methods This randomized single‐blind clinical trial was performed on 148 pregnant women who were candidates for induction of labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Overall, five RCTs 12 13 19 20 21 met the inclusion criteria, including a total number of 842 patients of which 414 were in the intervention group and 428 were in the control group. The included trials were performed in the following countries: two trials in Turkey, 12 19 one trial in Iran, 13 one trial in Pakistan, 20 and one trial in India. 21 An initial Bishop's score was assigned to all patients through cervical examination in the included trials.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, five RCTs 12 13 19 20 21 met the inclusion criteria, including a total number of 842 patients of which 414 were in the intervention group and 428 were in the control group. The included trials were performed in the following countries: two trials in Turkey, 12 19 one trial in Iran, 13 one trial in Pakistan, 20 and one trial in India. 21 An initial Bishop's score was assigned to all patients through cervical examination in the included trials.…”
Section: Resultsmentioning
confidence: 99%
“…Although it did not reach a statistically significant difference, it was considered to be clinically significant. 13 Another RCT by Shabir et al 20 demonstrated a significant decline in the labor duration with vaginal washing using normal saline prior to vaginal dinoprostone insertion during labor induction. Moreover, the rate of failure of labor induction and CS incidence were decreased among vaginal washing group in comparison with control group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations